2016
DOI: 10.1016/j.aquaculture.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of exogenous enzymes and probiotic on Nile tilapia (Oreochromis niloticus) growth, intestinal morphology and microbiome

Abstract: 15A study was carried out to investigate the combined effect of exogenous enzymes and 16 probiotic supplementation on tilapia growth, intestinal morphology and microbiome 17 composition. Tilapia (34.56 ± 0.05 g) were fed one of four diets (35% protein, 5% lipid); one 18 of which was a control and the remaining three diets were supplemented with either enzymes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
80
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 52 publications
6
80
3
6
Order By: Relevance
“…Growth performance and feed utilization efficiency were significantly improved by feeding Bacillus supplemented diets, implying a potential role of Bacillus probiotic in mitigating stress factors and promoting fish welfare. Similar findings have been observed in tilapia (Adeoye et al., ; Liu et al., ; Lukkana et al., ; Silva et al., ), gilthead sea bream ( Sparus aurata ) (Avella et al., ) and Eurasian perch ( perca fluviatilis L .) (Mandiki et al., ) fed Bacillus ‐based probiotics.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Growth performance and feed utilization efficiency were significantly improved by feeding Bacillus supplemented diets, implying a potential role of Bacillus probiotic in mitigating stress factors and promoting fish welfare. Similar findings have been observed in tilapia (Adeoye et al., ; Liu et al., ; Lukkana et al., ; Silva et al., ), gilthead sea bream ( Sparus aurata ) (Avella et al., ) and Eurasian perch ( perca fluviatilis L .) (Mandiki et al., ) fed Bacillus ‐based probiotics.…”
Section: Discussionsupporting
confidence: 77%
“…(Mandiki et al., ) fed Bacillus ‐based probiotics. Many studies (Adeoye et al., ; Avella et al., ; El‐Haroun et al., ; Liu et al., ; Lukkana et al., ; Mandiki et al., ; Silva et al., ; Taoka et al., ) demonstrated the ability of Bacillus to colonize the gut of fish and accordingly enhance the production of organic acids, activation of digestive enzymes and detoxification of the harmful constituents of feeds and collectively maintain a healthy gut with a subsequent improvement in nutrient digestibility and absorption. Recently, it was demonstrated that Bacillus can displace pathogenic bacteria from the gut and accordingly enhance disease resistance and improve fish performance (Addo et al., ; Hostins et al., ; Srisapoome & Areechon, ).…”
Section: Discussionmentioning
confidence: 99%
“…promotes decomposition of consumed organic debris, phytoplankton, or zooplankton (Borsodi et al., ). This species was also common in intestinal tracts of goldfish, common carp, grass carp, ayu, tilapia, zebrafish, rainbow trout, channel catfish, largemouth bass, and bluegill (Adeoye et al., ; Etyemez & Balcázar, ; Larsen, Mohammed, & Arias, ; Roeselers et al., ; Tsuchiya, Sakata, & Sugita, ; Van Kessel et al., ). However, the effects of this species have never been tested in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was conjectured that the reason for this situation was that the experimental fish obtained sufficient protein in this experimental diet and did not need more carbohydrates to be absorbed as energy materials. However, Adeoye et al () found no improvement in Nile tilapia ( Oreochromis niloticus ) growth performance by adding multienzyme complex composed of phytase (7.5 mg), protease (30 mg) and xylanase (25 mg) in diets. Furthermore, the improvement of growth performance in yellow perch ( Perca flavescens ) was not observed in the experiment of done by Kolkovski, Yackey, Czesny, and Dabrowski () using microdiet supplementation of 1 g/kg dietary digestive enzymes.…”
Section: Discussionmentioning
confidence: 92%